Kedudukan Fatwa DSN-MUI dalam Transaksi Keuangan pada Lembaga Keuangan Syariah di Indonesia - Awaluddin Awaluddin; Andis Febrian (Alhurriyah, 2020)
National Sharia council fatwa is a reference by every sharia financial institution in Indonesia in carrying out its operations. To implement sharia compliance by sharia financial institutions as formed as an extension of the DSN to oversee every financial institution to be in line with sharia principles. A problem that often arises in Islamic financial institutions is that the fatwa issued by DSN requires studies and opinions from DPS in operational techniques in Islamic financial institutions. the existing fatwas have not yet been represented in technical transactions at financial institutions. This research is a sociological juridical study, which examines the existence of MUI fatwas and the development of sharia economy and how the legal relationship between the MUI fatwa and the implementation of sharia economy in Indonesia with applicable laws and regulations. The results of this study see that the position of the fatwa in the perspective of banking law in Indonesia as a juridical reason for the legislature to set in the legislation. Besides that, the DSN fatwa as a technical basis for supervision is regulated in the laws and regulations on Islamic banking. From the data obtained that the position of fatwa in sharia banking has become a reference in every transaction for the future, each DPS in sharia financial institution is expected to not only be an independent board that is complementary but has a special position and staff in charge of each transaction carried out in the hope of implementing Sharia principles are maximally implemented. Fatwa dewan syariah nasional merupakan rujukan oleh setiap lembaga keuangan syariah di Indonesia dalam menjalankan opersionalnnya. Untuk menjalankan kepatuhan syariah oleh lembaga keuangan syariah maka dibentuklah Dewan Pengawas Syariah (DPS) sebagai perpanjangan tangan dari Dewan Syariah Nasional (DSN) untuk mengawasi setiap lembaga keuangan untuk sejalan dengan prinsip syariah. Problem yang sering muncul di lembaga keuangan syariah adalah fatwa yang dikeluarkan oleh DSN membutuhkan kajian dan opini dari DPS dalam teknis operasional di lembaga keuangan syariah. Fatwa yang sudah ada belum semuannya terwakili dalam teknis transaksi pada lembaga keuangan. Penelitian ini merupakan suatu penelitian yuridis sosiologis, yaitu meneliti tentang keberadaan Fatwa-fatwa MUI dan perkembangan ekonomi syariah dan bagaimana hubungan hukum antara fatwa MUI dan pelaksanaan ekonomi syariah di Indonesia dengan peraturan perundang-undangan yang berlaku. Hasil penelitian ini melihat bahwa kedudukan fatwa dalam prespektif hukum perbankan di Indonesia sebagai alasan yuridis bagi lembaga legislasi untuk menetapkan dalam aturan perundang-undangan. Disamping itu juga fatwa DSN sebagai dasar teknis pengawasan yang diatur dalam aturan perundang-undangan tentang perbankan syariah. Dari data yang diperoleh bahwa kedudukan fatwa pada perbankan syariah sudah menjadi rujukan dalam setiap transaksi untuk kedepannya setiap DPS yang ada dilembaga keuangan syariah diharapkan tidak hanya sebagai dewan independen yang besifat sebagai pelengkap tetapi memiliki kedudukan dan staf khusus yang membidangi setiap transaksi yang dijalankan dengan harapan pelaksanaan prinsip syariah maksimal dilaksanakan.